The Minor Prophets: a theological introduction - Bartholomew, Craig G. (IVP Academic, An imprint of InterVarsity Press, 2023)
"In this unique introduction to the Minor Prophets, two biblical scholars survey the twelve books and explore the theological themes of each. Filled with helpful exegetical insights, this books is an invaluable guide for students, pastors, and scholars looking for a cohesive exploration of these often-overlooked books of the Hebrew Bible"--